2018
DOI: 10.1002/cam4.1555
|View full text |Cite
|
Sign up to set email alerts
|

Serum SP70 is a sensitive predictor of chemotherapy response in patients with advanced nonsmall cell lung cancer

Abstract: SP70 is a novel tumor biomarker in patients with nonsmall cell lung cancer (NSCLC). However, its role as a marker for predicting the response to chemotherapy for patients with advanced NSCLC has not been investigated. A total of 152 patients were enrolled. Serum SP70, carcinoembryonic antigen (CEA), cytokeratin 19 fragment (CYFRA21‐1), and neuron‐specific enolase (NSE) were detected before and after 2 cycles of chemotherapy. The correlation between serum tumor biomarker levels and chemotherapy responses and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…12,13 SP70 antigen exists in the cytoplasm and envelope of NSCLC cancer cells, and is a potential carcinomatous standard of NSCLC. 14 It was shown that the antigen positive rates of CEA, CA125 and SP70 in pleural effusion specimens in the malignant group were higher than those in the benign group, indicating that CEA, CA125 and SP70 antigens were highly expressed in the malignant pleural effusion. Subsequent ROC curve analysis showed that Wanyu Yan et al all indexes of pleural effusion could diagnose NSCLC combined with malignant pleural effusion, which was partially consistent with previous studies.…”
Section: Discussionmentioning
confidence: 91%
“…12,13 SP70 antigen exists in the cytoplasm and envelope of NSCLC cancer cells, and is a potential carcinomatous standard of NSCLC. 14 It was shown that the antigen positive rates of CEA, CA125 and SP70 in pleural effusion specimens in the malignant group were higher than those in the benign group, indicating that CEA, CA125 and SP70 antigens were highly expressed in the malignant pleural effusion. Subsequent ROC curve analysis showed that Wanyu Yan et al all indexes of pleural effusion could diagnose NSCLC combined with malignant pleural effusion, which was partially consistent with previous studies.…”
Section: Discussionmentioning
confidence: 91%
“…In this study, we first reported the role of SP70 in the diagnosis and prognosis of HCC. As a new potential biomarker, SP70 has been proved to be valuable in lung cancer and gastric cancer detection in previous studies ( 11 , 19 ), while its expression and clinical value in HCC have not been studied. Our results showed the SP70 protein was mainly localized on the membrane and in the cytoplasm of HCC cells, and its expression in HCC tissues was stronger than in adjacent tissues and normal liver tissues.…”
Section: Discussionmentioning
confidence: 99%
“…As a tumor derived antigen, SP70 is widely involved in the regulating the expression of numerous genes (GEO accession number: GSE59655), promoting cancer cell proliferation and metastasis. Serum SP70 levels were significantly correlated with tumor differentiation and lymph node metastasis and played an important role in cancer chemotherapy monitoring ( 11 , 12 ). Moreover, SP70-targeted imaging was found to be able to markedly improve the detection of lung adenocarcinoma detection ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Monoclonal antibody (mAb) NJ001, which has high affinity and specificity for NSCLC cells, was generated in our laboratory. 4,5 Our previous studies showed that mAb NJ001 has effective antitumor activity both in vitro and in vivo. 5 However, the effect of NJ001 on invasiveness and metastasis in lung adenocarcinoma (AD) has not yet been defined.…”
Section: Introductionmentioning
confidence: 99%